Β-tungsten: a promising metal for spintronics. (3rd July 2018) - Costa, M; Costa, A T; Hu, J; Wu, R Q; Muniz, R B
Abstract: Ultrathin films of β -tungsten provide very promising substrates for applications in spintronics, and the possibility of incorporating them into multilayers extends such expectations. Our calculations indicate that it is viable to deposit a single layer of Mn on two non-equivalent (0 0 1) surfaces of β -tungsten that have easy axes along orthogonal directions [0 1 0] and [1 0 0], respectively. The ferromagnetic structure of this Mn monolayer adsorbed to either of those surfaces displays a giant in-plane magneto-crystalline anisotropy that exceeds 12 meV per Mn atom. Furthermore, when coated with additional layers of β -tungsten the magnetization easy axis becomes perpendicular to the planes. We envisage that magnetic multilayers involving mono-crystalline thin films of β -tungsten oriented along high-symmetry directions offer a very fruitful playground for spintronic applications.